ANALISIS PERLAKUAN AKUNTANSI SYARIAH PADA TRANSAKSI MURABAHAH BERDASARKAN PSAK 102 DI BMT MUSLIMAH MASYITHAH KOTA JAMBI - Siska Jannah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims 1.To find out how the murabahah financing mechanism is at BMT Muslimah Masyithah Jambi City and 2. To analyze how the recognition, measurement, presentation, and disclosure of murabahah transactions are based on PSAK 102 at BMT Muslimah Masyithah Jambi City. This thesis uses qualitative research methods with research data obtained through interviews and documentation by taking sources from the manager and treasurer of BMT Muslimah Masyithah Jambi City. The data analysis used in this research is descriptive qualitative technique. The results of this study indicate that the Murabahah practice carried out by BMT with a pure murabahah and murabahah bil wakalah system is in accordance with the Shari'a. BMT in implementing murabahah bil wakalah, murabahah contracts and wakalah contracts are carried out separately. Murabahah accounting treatment carried out by BMT Muslimah Masyithah Jambi City is only a small part that is in accordance with PSAK Number 102. However, there are some things that are not in accordance with PSAK Number 102, namely the practice of BMT Muslimah Masyithah Jambi City does not record any journal or there is no related accounting treatment wakalah contracts, advances, and supplies/assets of murabahah, presentation of murabahah receivables is not in accordance with PSAK 102, and presentation of financial statements is not fully in accordance with PSAK Number 102.